The Determinants of Risk Disclosure in the Aviation Industry - XU, MENGYANG (2019)
Risk disclosure has attracted more and more attentions from stakeholders and scholars. However, there is currently no relevant research on risk disclosure in the aviation industry. Therefore, under this background, this paper studies the determinants of risk disclosure in the aviation industry. This paper selects 113 sample data from 48 airlines worldwide and analyzes the factors that may affect the risk information disclosure in the airline's annual report between 2014 and 2017. Through the regression analysis of previous studies, six factors were selected for analysis, namely board size, firm size, board independence, CEO duality, profitability and safety rating. The results of this paper show that, the board independence and the board size will have a decisive impact on risk disclosures in the aviation industry, and both impacts are negative. This may be because the number of independent non-executive directors on the board can reflect the risk management capabilities of a company. In addition, the board size may reduce the efficiency of the internal decision-making process, which may in turn impair the supervisory function of the board. This dissertation also found that safety rating and CEO duality may also influence the risk disclosure to a certain extent. However, this paper did not find a significant correlation between firm size and risk disclosures or and profitability and risk disclosures.